The world at war [videorecording (DVD)] - Olivier, Laurence, 1907-1989 (A&E Home Video ; Distributed by New Video, 2004)
An extraordinary collection of newsreel, propaganda, and home-movie footage drawn from the archives of 18 nations, including color close-ups of Adolf Hitler taken by his mistress, that present an unvarnished perspective of the war's pivotal events. Penetrating interviews with eyewitness participants - from Hitler's secretary to Alger Hiss to ordinary citizens who stood outside the battle lines - and spine-tingling, first-hand accounts to an already unforgettable experience.